2021
DOI: 10.1007/s40261-021-01092-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Interferon-β in Moderate-to-Severe Hospitalised Cases of COVID-19: A Systematic Review and Meta-analysis

Abstract: Background and Objective Interferon-β, as with several other anti-viral agents, has been investigated as a treatment option for COVID-19 as a repurposed drug. The present study is a systematic review and meta-analysis of interferon-β to determine its efficacy among moderate-to-severe COVID-19 patients. Methods A systematic literature search was done using relevant terms for ‘COVID-19’ and ‘interferon-β’. Randomised controlled trials (RCT) evaluating the efficacy of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Previous reviews have several limitations with regard to the evaluation of IFN efficacy in the treatment of COVID-19. Previous meta-analyses were restricted to IFN-β [ 37 , 38 ], and data synthesis of the included studies did not consider the study design, such as retrospective observational/cohort and RCT, leading to imprecision in estimating the effect estimate of IFN [ 39 ]. A major limitation of previous reviews was that they evaluated the efficacy of IFN therapy in heterogeneous patients with different severities of COVID-19 [ 37 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews have several limitations with regard to the evaluation of IFN efficacy in the treatment of COVID-19. Previous meta-analyses were restricted to IFN-β [ 37 , 38 ], and data synthesis of the included studies did not consider the study design, such as retrospective observational/cohort and RCT, leading to imprecision in estimating the effect estimate of IFN [ 39 ]. A major limitation of previous reviews was that they evaluated the efficacy of IFN therapy in heterogeneous patients with different severities of COVID-19 [ 37 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Kumar S. et al. (2021) ( 20 ) conducted a meta-analysis of IFN-β to determine its effect on moderate-to-severe COVID-19 patients. Seven randomized controlled trials (RCTs) were permitted to perform a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Separate clinical trials have found different outcomes for IFN treatment in COVID-19 ( 18 ). There are several meta-analyses on the efficacy of IFN-β ( 19 , 20 ), but there are no such data on IFN-α that has a wide range of antiviral properties and is used as a first-line drug in the treatment of various viral diseases. Since we need more information about possible treatments for Covid-19, and there is not enough data on the potential of IFN -α against Covid-19, this meta-analysis allows us to understand the effectiveness of this line of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…One hallmark of COVID 19 pathophysiology is disruption of normal interferon signaling [ 99 , 100 ]. Nonetheless, the WHO Solidarity trial [ 101 ] and studies of interferon-β [ 102 ] and pegylated interferon lambda [ 103 ] have shown interferon treatment does not reduce COVID-19 mortality.…”
Section: Treatments Targeting the Virusmentioning
confidence: 99%